2018
DOI: 10.21071/az.v0i0.3879
|View full text |Cite
|
Sign up to set email alerts
|

Efectos del aceite esencial de Eucalyptus globulus cargado en nanoemulsiones y en nanocápsulas en la reproducción de la garrapata bovina (Rhipicephalus microplus)

Abstract: La infestación por garrapatas (Rhipicephalus microplus), genera importantes pérdidas en la producción bovina. El objetivo de este estudio fue investigar si el aceite esencial de Eucalyptus globulus en diferentes nanosistemas (nanoemulsiones y nanocápsulas) es capaz de potenciar el efecto negativo sobre la reproducción de la garrapata, interfiriendo en su oviposición y eclosión de los huevos. Las hembras engordadas de R. microplus se obtuvieron de vacas naturalmente infestadas. En condiciones experimentales, es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…Also, some previous works showed that adult ticks are signi cantly more resistant than larva [32,33]. In line with our results, nanostructured forms of Eucalyptus globulus was not effective on the reproduction of Rhipicephalus microplus [34]. Similar data reported after using Tea tree and lemon nano oils on adult female of R. annulatus [35] and nano EO of Cinnamomum verum on R. microplus [36].…”
Section: Discussionsupporting
confidence: 89%
“…Also, some previous works showed that adult ticks are signi cantly more resistant than larva [32,33]. In line with our results, nanostructured forms of Eucalyptus globulus was not effective on the reproduction of Rhipicephalus microplus [34]. Similar data reported after using Tea tree and lemon nano oils on adult female of R. annulatus [35] and nano EO of Cinnamomum verum on R. microplus [36].…”
Section: Discussionsupporting
confidence: 89%
“…It is noteworthy that the current EO nanoemulsions displayed lower activity levels than the pure oils against adult ticks. Galli et al [34] reported similar levels of effectiveness for pure, nanoemulsion, and nanocapsule forms of Eucalyptus globulus EO against Rhipicephalus microplus ticks. This result can be explained by the fact that a variety of factors, such as the temperature, storage time, pH, and ionic strength, have negative impacts on nanoemulsion stability.…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, after 20 days, the cows that were previously infested and treated with the nanoemulsion were free of the parasites [49]. Similar work done by Galli et al [50] and contributors with Eucalyptus globulus nanoemulsion showed that the formulations at 1% and 5% inhibited parasite reproduction by 50% and 61.2%, respectively. All oil nanoemulsions with acaricidal activity are shown in Table 2.…”
Section: Biological Activities Of Essential Oil Nanoemulsionsmentioning
confidence: 74%